Single Low-Volume Center Experience with Frozen Elephant Trunk in Acute Type A Aortic Dissections - López Almodóvar, Luis F.; Lima Cañadas, Pedro; Enríquez Puga, Andrés; Narváez Mayorga, Irene; Buendía Miñano, José A.; Sánchez Casado, Marcelino; Cañas Cañas, Alfonso (AORTA, 2018)
Background Acute Type A aortic dissection (AAAD) is a surgical emergency. In patients with arch and descending aorta involvement (DeBakey Type I), a total aortic arch replacement with frozen elephant trunk (FET) could favor false lumen thrombosis and improve long-term results. The authors hereby present their experience with this technique in a single low-volume center, to assess whether the technique is feasible to treat such disease.Methods From January 2011 to December 2016, 43 patients with AAAD were operated on in the authors' institution, which carries out 300 to 350 annual procedures. Among these, 12 patients with an intimal tear in the aortic arch and/or proximal descending aorta received a FET procedure (10 males, age 57 years). Concomitant procedures were aortic valve replacement (42%), Bentall (25%), and aortic valve repair (17%).Results Cardiopulmonary bypass, cardiac arrest, and circulatory arrest times were 235 ± 43, 171 ± 33, and 75 ± 20 minutes, respectively. The operative mortality was 16.7% (n = 2). Stroke and re-thoracotomy for bleeding occurred in 8% (n = 1) and 8% (n = 1), respectively. There was no spinal cord injury. Follow-up was 36.1 months. During follow-up, no patients died or required a reoperation on the downstream aorta.Conclusion Although all patients were operated on in a low-volume center, the results with FET in AAAD are acceptable. Even though this technique demands high technical skills, it is a promising approach in patients with acute aortic dissection.
Keywords: aortic dissection; aorta; frozen elephant trunk